Ethnoracial Diversity across the Rural-Urban Continuum. Issue 1 (July 2017) - Lee, Barrett A.; Sharp, Gregory
Scholarship and popular opinion regard cities as more racially and ethnically diverse than rural communities. However, recent trends hint at the possibility of less distinctive diversity profiles on either side of the metro-nonmetro divide. To explore this, we compare the magnitude and structure of ethnoracial diversity in more than 27, 000 census-defined places arrayed across ten different types of county contexts that spanned the rural-urban continuum in 2010. Even as average residents' exposure to diversity steadily declines as contexts become more rural and remote, place-based (unweighted) results show an uneven pattern of diversity across most of the continuum. Multivariate analysis supports the unevenness scenario: when place characteristics are taken into account, many of the associations between type of context and diversity weaken to the point of nonsignificance. Taken together, these findings suggest a blurring of rural-urban boundaries with respect to community ethnoracial composition.